Employee‐Driven Sustainability Performance Assessment in Public Organisations. (29th July 2017) - Coutinho, Vera; Domingues, Ana Rita; Caeiro, Sandra; Painho, Marco; Antunes, Paula; Santos, Rui; Videira, Nuno; Walker, Richard M.; Huisingh, Donald; Ramos, Tomás B.
Abstract: Organisations are increasingly adopting sustainability performance assessment tools. However, these formal organisational sustainability assessments are typically managed and prepared by technical staff. There is a lack of research on approaches that enable a stakeholder‐driven performance assessment. This paper develops a framework of informal/complementary stakeholder‐driven sustainability performance assessment, from the perspective of employee voluntary collaboration. The framework composes a checklist of questions covering the main sustainability domains: perceptions, individual practices, and voluntary monitoring indicators. In an exploratory case study in a public organisation, the checklist was evaluated by employees in a participatory workshop. The evaluation criteria of understanding and usefulness were rated more positively than reliability . This paper shows a novel way of integrating employee inputs for informal sustainability assessment and supports the importance of empowering public organisations, thereby increasing their understanding of sustainability management frameworks. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment